Inicjatywy w zakresie zwalczania oszustw karuzelowych w Unii Europejskiej - Hybka, Małgorzta Magdalena (Initiatives to Combat Carousel Fraud in the European Union, 2009)
The article provides an overview of the recent initiatives against carousel fraud in the European Union. The author focuses on the following anti-fraud measures: VAT reverse charge system, European Carousel Network and the proposed modifications to articles 143(d) and 205 of the Council Directive 2006/122/EC. Furthermore, the article presents the mechanism of carousel fraud and the scale of this fraud on the basis of data for the United Kingdom published by the HM Revenue & Customs. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 68-75